HUBUNGAN ANTARA KONSEP DIRI DENGAN PERILAKU SOSIAL ANAK DI TK HARAPAN MAJU SIBIRUANG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Sakina, Ulfat; Novianti, Ria; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was motivated by childhood since children have learned how to behave socially in accordance with the expectations of those who are closest to him, namely his mother, father, siblings, and other family members. Such as family relations between the father and mother who are not harmonious, often fight in front of children, harsh treatment of children, too strict and curb children's freedom, all of which will greatly affect the development of children's personality and self-concept of children. The objectives of this study are: 1) To determine the self-concept of children aged 5-6 years in Harapan Maju Sibiruang Kindergarten, Koto Kampar Hulu District, Kampar District. 2) To find out the social behavior of children aged 5-6 years in Harapan Maju Sibiruang Kindergarten, Koto Kampar Hulu District, Kampar District. 3) To determine the relationship between self-concept and social behavior of children aged 5-6 years in Harapan Maju Sibiruang Kindergarten, Koto Kampar Hulu District, Kampar District. The population in this study were all children in Harapan Maju Sibiruang Kindergarten Kamapar Kampar Hulu Subdistrict, Kampar Regency, as many as 27 teachers consisting of 3 classes. This type of research is correlative quantitative research. The sample in this study were 27 children. Based on hypothesis testing from the results of product moment correlation analysis, the value of rxy is 0.703. Correlation is interpreted using the table of r product moment values. From the calculation it is known that r count> r table for a significant level of 5% = 0.437> 0.273. This means that Ha can be accepted and Ho is rejected. It can be concluded that self-concept with social behavior has a positive relationship. The results of the calculation of the coefficient of determination are known that the self concept with social behavior of children in Harapan Maju Sibiruang Kindergarten Koto Kampar Hulu District is 49%, meaning that children's self-concept determines 49% of their social behavior while 50.6% of social behavior is determined by other variables.Key Words: Self concept, social behavior